Comparison of the effect and durability of foot massage methods on the balance of the blindness - Kamal Mohammadkhani; Yousef Moghaddas Tabrizi; Mohammad Karimizadeh Ardakani; Mohammad Hani Mansouri (Islamic Azad University, Hamedan Branch, 2021)
Objective: Weakness in the sensory-deep receptors of the sole is one of the essential factors in lower limb movement disorders and balance in blindness. Therefore, this study aimed to compare the effect and durability of foot massage techniques on the balance of the blindness Methods: The present study was a one-way blind with a pretest-posttest design. The statistical sample consisted of 30 blind boys aged 20-30 years randomly divided into three groups of 10 people. The protocol of massage methods was performed on the samples for 21 days. Biodex balance system was used to evaluate the balance. The normality of the data was analyzed using the Shapiro-Wilk test. The analysis of variance with repeated measures was used to analyze the differences within the group. The ANOVA test was used to examine the differences between the groups at the significance level of 0.05. Results: The results of the intra-group test showed that all three methods of foot massage improved static and dynamic balance in the blind (P<0.001). The results of the ANOVA test for comparison between groups showed no significant difference between the three methods of foot massage on static balance and posterior-anterior index of dynamic surface and internal-external index of dynamic surface (P>0.05) only on the general surface index. There is a significant difference in the dynamics of hand massage compared to the other two massages (P<0.001). Conclusion: Due to the significant effect of foot massage methods on the balance of the blind, foot massage can be used as an effective factor in strengthening the sensory receptors of the foot and ultimately improving the balance of the blind.